Inverse association between serum iron levels and Hashimoto’s thyroiditis in United States females of reproductive age: analysis of the NHANES 2007–2012 - Zhang, Liang; Li, Yibing; Yang, Liu; Luo, Zhixiong; Wu, Zhaoyu; Wang, Jingbo; Qin, Siyuan; Ren, Fei; Hu, Tianyuan (Frontiers in Nutrition, 2024)
Purpose Hashimoto's thyroiditis (HT) is a significant public health concern, particularly among females. While existing studies have explored the correlation between serum iron levels and HT, limited research has specifically focused on this association in reproductive-age females. Our study aims to investigate the relationship between serum iron and HT.Using data from the National Health and Nutrition Examination Survey (NHANES) database (2007)(2008)(2009)(2010)(2011)(2012), we employed weighted multivariate logistic regression models, an XGBoost model, and smooth curve fitting. We assessed the correlation between serum iron and HT and examined linear and non-linear relationships with thyroid peroxidase antibodies (TPOAb) and thyroglobulin antibodies (TgAb).Among 2356 participants, each unit increase in serum iron was associated with a 43% reduced risk of HT (Odds Ratios (OR) 0.574; 95% Confidence Interval (CI) 0.572, 0.576). Quartile analysis confirmed these effects. The XGBoost model identified serum iron as the most significant variable correlated with HT. Smooth curves revealed a linear association between log2-transformed serum iron and HT. Additionally, log2-transformed serum iron inversely correlated with TPOAb levels (β -15.47; 95% CI -25.01, -5.92), while a non-linear relationship was observed with TgAb.Our study reveals that in reproductive-age women, every unit increase in serum iron is associated with a 43% lower risk of HT, demonstrating an inverse relationship. Additionally, serum iron exhibits a negative correlation with TPOAb and a non-linear association with TgAb.